2000
DOI: 10.1016/s0377-1237(17)30218-6
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Hernia Through Nonvertical Incisions

Abstract: Although uncommon, incisional hernia may occur after operations where vertical or paramedian incision is not used. Fifteen patients of incisional hernia through nonvertical incisions in the age group of 22 to 65 years were studied. This included hernia through subcostal incision commonly used for cholecystectomy, gridiron incision, pfannensteil incision and lumbar incisions. Majority of these hernias were due to wound complications and factors which give rise to an increased strain on suture lines. Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…In other studies [2,3,8] , incisional hernias were seen in midline incisions followed by transverse incisions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In other studies [2,3,8] , incisional hernias were seen in midline incisions followed by transverse incisions.…”
Section: Discussionmentioning
confidence: 85%
“…Pain usually disappeared after 3-4 days postoperatively. Complications (noted mostly in small case series or case reports) [8,[22][23][24][25] were mainly attributed to extensive dissection of the surgical field. They could have been avoided by the interposition of the greater omentum, absorbable mesh or Seprafilm placed in between the PP mesh and the intestinal loop.…”
Section: Discussionmentioning
confidence: 99%
“…Ellis reported a decrease in the incidence of an incisional hernia with mass closure, which is consistent with our study [6].However, Bucknall et al [4] reported no significant difference in the incidence of incisional hernias. Singh et al [23] reported no case of an incisional hernia in mass closure and 6.6% in conventional layered closure. Single layer closure had reduced operative time than conven- tional layered closure, and hence, prevents anaesthetic hazards, reduces the cost of anaesthetic agents and saves the time of the surgeon.…”
Section: Resultsmentioning
confidence: 98%
“…An incisional hernia occurs due to wound complications such as seroma, wound infection and faulty closure technique [23].Mass closure method reduces the time required for closure of incision and incidence of wound dehiscence and the incidence of an incisional hernia [24].An incisional hernia is a frequent complication of abdominal wall closure with a reported incidence of between 5% and 15% following vertical midline incisions at one-year follow-up [25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The repair of incisional hernias following liver transplantation constitutes a major surgical challenge [14,[24][25][26][27]. Approximately 30% of the abdominal wall repairs in our institution are performed for transverse hernias, 19% of these in liver transplant recipients [13].…”
Section: Discussionmentioning
confidence: 99%